2016
DOI: 10.3127/ajis.v20i0.1110
|View full text |Cite
|
Sign up to set email alerts
|

Good Old Gamers, Good Drivers: Results from a correlational experiment among older drivers

Abstract: In many situations, driving is essential for senior citizens to maintain their independent lifestyle. A systematic literature review was conducted that summarized the age-related physical, visual and cognitive functional declines and their associated risk to driving. Based on these findings, we explored whether the skills required in playing Xbox Kinect video games were correlated with measures of driving performance among older drivers. Fifty-two participants, 65 years of age or older (Mean = 72; SD = 3.84; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(24 reference statements)
2
6
1
1
Order By: Relevance
“…A number of participants who expressed some initial scepticism about the telehealth equipment, were very accepting of the equipment by the follow-up interview. This is in line with other studies that have introduced information systems to older people (Burmeister, 2010(Burmeister, , 2012Kurniawan, 2008;Morris et al, 2014;Vichitvanichphong, Talaei-Khoei, Kerr, Ghapanchi, & Scott-Parker, 2016). There seemed to be relatively few technical problems with reliability, but some follow-up reminders to measure and report according to the agreed schedule had occurred.…”
Section: Economic Impactssupporting
confidence: 88%
“…A number of participants who expressed some initial scepticism about the telehealth equipment, were very accepting of the equipment by the follow-up interview. This is in line with other studies that have introduced information systems to older people (Burmeister, 2010(Burmeister, , 2012Kurniawan, 2008;Morris et al, 2014;Vichitvanichphong, Talaei-Khoei, Kerr, Ghapanchi, & Scott-Parker, 2016). There seemed to be relatively few technical problems with reliability, but some follow-up reminders to measure and report according to the agreed schedule had occurred.…”
Section: Economic Impactssupporting
confidence: 88%
“…The recently published paper by Vichitvanichphong, Talaei-Khoei, Kerr, Ghapanchi, and Scott-Parker (2016), is interesting because their findings are contrary to previous research which reported that playing video games skills did not transfer to driving. Their review of the literature showed that functional declines related to driving ability in many cases result in accidents that could be avoided if particular video games were used to test the abilities of elderly drivers.…”
Section: Reviewcontrasting
confidence: 67%
“…(Ballesteros et al, 2014;Basak et al, 2008;Charness, 2015;Maillot et al, 2012;McDougall and House, 2012;Zelinski and Reyes, 2009)  The effect of video game trainings on the cognitive ability of elderly persons can be transferred to the capabilities required for the daily life activities of elderly, making their independent life possible. (Maillot et al, 2012;Damian Sue et al, 2014;Vichitvanichphong et al, 2016) Perceived Transfer Effect When an individual perceives the usefulness of an intervention through understanding its transfer effect that allows her/him to remain capable of living independently in a standard of living that she/he values.…”
Section: Transfer Effectmentioning
confidence: 99%
“…There is a large body of literature that supports video games by showing the positive impacts on elderly's cognitive ability tests; tests such as Wisconsin Card Sorting (Ballesteros et al, 2014), Stroop task (Zelinski and Reyes, 2009), Operation Span (Basak et al, 2008) and Letter-Number Sequence (Charness, 2015), Digit Span (McDougall and House, 2012), and Simple Reaction Time (Maillot et al, 2012). It was also shown that the effect of video game trainings on the cognitive abilities of the elderly can be transferred to the capabilities required for daily activities that make their independent life possible (Maillot et al, 2012;Damian Sue et al, 2014;Vichitvanichphong et al, 2016).…”
Section: Perceived Transfer Effectmentioning
confidence: 99%
See 1 more Smart Citation